Effects of different secondary vegetation types on bat community composition in Central Amazonia, Brazil - Bobrowiec, Paulo Estefano Dineli; Gribel, Rogério (Animal Conservation, 2010)
The process of secondary succession on degraded lands in the Amazon depends on their land-use histories. In this scenario, little is known about how animal communities respond to different types of secondary vegetation in the region. We examined the effects of abandoned cattle pasture, Vismia- and Cecropia-dominated regrowth on the abundance of bat species and community composition in the Central Amazon, Brazil, based on 11 netting sites and on landscape characteristics. We captured 1444 bats, representing 26 species and two families (Phyllostomidae and Mormoopidae). Among the six most-captured Phyllostomidae bats, Sturnira lilium and Sturnira tildae had significantly higher capture rates in abandoned pasture, while Rhinophylla pumilio predominated in both Vismia- and Cecropia-dominated regrowth. An hybrid multidimensional scaling ordination revealed significant differences in the bat community among the three types of secondary vegetation. Phyllostominae bats were more common and richer in the less-disturbed areas of Cecropia-dominated regrowth, while Stenodermatinae species were more captured in abandoned pastures. Our results suggest that the type of secondary vegetation, together with its land-use history, affects bat community composition in the Central Amazon. The Phyllostominae subfamily (gleaning animalivores) was habitat selective and disappeared from areas experiencing constant disturbances. On the other hand, Stenodermatinae frugivorous bats often used and foraged in altered areas. We suggest that secondary vegetations in more-advanced successional stages can be used to augment the total area protected by forest conservation units. © 2009 The Authors. Journal compilation © 2009 The Zoological Society of London.
Keywords: Bat; Community Composition; Habitat Creation; Ordination; Restoration Ecology; Revegetation; Secondary Forest; Amazonia; Brasil; Animalsia; Bos; Cecropia; Chiroptera; Lilium; Mormoopidae; Phyllostomidae; Phyllostominae; Rhinophylla Pumilio; Stenodermatinae; Sturnira Lilium; Sturnira Tildae; Vismia